High-quality InP/ZnS nanocrystals with high photometric performance and their application to white quantum dot light-emitting diodes - Yang, Xuyong (2013)
Full visible range covering InP/ZnS core-shell nanocrystals with high photometric performance have been prepared. Making use of these nanocrystals, we demonstrate a white quantum dot LED with a high color rendering index of 91.